Combined Effects of Warming and Grazing on Rangeland Vegetation on the Qinghai-Tibet Plateau - Chen, Chen; Li, Tiejian; Sivakumar, Bellie; Sharma, Ashish; Albertson, John D.; Zhang, Li; Wang, Guangqian (Frontiers in Environmental Science, 2021)
Climate warming has increased grassland productivity on the Qinghai-Tibet Plateau, while intensified grazing has brought increasing direct negative effects. To understand the effects of climate change and make sustainable management decisions, it is crucial to identify the combined effects. Here, we separate the grazing effects with a climate-driven probability model and elaborate scenario comparison, using the Normalized Difference Vegetation Index (NDVI) of the grassland on the Qinghai-Tibet Plateau. We show that grazing has positive effects on NDVI in the beginning and end of the growing season, and negative effects in the middle. Because of the positive effects, studies tend to underestimate and even ignore the grazing pressure under a warming climate. Moreover, the seasonality of grazing effects changes the NDVI-biomass relationship, influencing the assessment of climate change impacts. Therefore, the seasonality of grazing effects should be an important determinant in the response of grassland to warming in sustainability analysis.